Transformation of the Islamic Religious Education Curriculum in the Digital and Globalization Era - Sofiatun Anisa; Nur Khasanah (TATHO: International Journal of Islamic Thought and Sciences, 2026)
This study identifies the transformation of the Islamic Religious Education curriculum by integrating Islamic epistemology, digital pedagogy, and ethical considerations relevant to the Society 5.0 era. Using an integrative literature review, the study synthesizes theoretical perspectives and empirical findings from recent national and international research. The results show that although digital transformation offers opportunities for interactive, collaborative, and technology-enhanced learning, it also presents challenges such as fragmented religious understanding, exposure to unverified online content, limited teacher digital competence, and emerging digital ethical issues among students. These conditions highlight the urgent need for curriculum reconstruction that remains rooted in Islamic epistemic values. The study proposes three essential directions for strengthening curriculum transformation: the integration of classical Islamic epistemology, alignment with digital pedagogical models, and embedding Islamic digital ethics as a core component of learning. This reconstruction is expected to produce learners who are spiritually grounded orientation that optimizes cognitive, affective, and psychomotor, digitally literate, and capable of navigating global challenges responsibly.